A Structured, Anatomy-Based Chest CT Interpretation Curriculum for Pulmonary Fellows Covering the Main Patterns of Parenchymal Lung Disease - Laura Granados; Julie Takasugi; James Town; Rosemary Adamson (MedEdPORTAL)
Introduction Chest computed tomography (CT) interpretation is a key competency for pulmonary fellows, with many resources intended for radiologists but very few for this specific group. We endeavored to create a curriculum to teach chest CT interpretation to first-year pulmonary fellows. Methods We assembled a team of two pulmonologists, one radiologist, and a fellow with computer drafting software experience. We reviewed the literature, used principles of cognitive load theory to outline the content of our curriculum, collected original CT images exemplifying key patterns of disease, created original illustrations using computer drafting programs, and outlined frameworks to identify chest CT patterns and build differential diagnoses. We divided the material into five short videos and provided 18 practice cases to be reviewed asynchronously. We then organized a 1-hour in-person review session facilitated by a chest radiologist. We created a survey to assess our curriculum. The material presented here has been delivered to three consecutive classes of first-year pulmonary and critical care medicine fellows at our institution. Results Nineteen fellows in three cohorts reviewed the curriculum. Twelve fellows (63% response rate) completed the postcurriculum survey. Overall, there was a significant improvement in comfort, with the calculated paired sample t test showing a mean comfort of 3.2 precurriculum and a mean comfort of 4.5 postcurriculum (p < .001). Discussion This self-guided, interactive curriculum provides a structured approach connecting key lung anatomy to patterns of disease and is an effective way to teach chest CT interpretation to pulmonary fellows.